PERBEDAAN TERAPI TILAWAH DAN TERAPI MURROTAL TERHADAP TINGKAT STRES MAHASISWA TINGKAT AKHIR STIKES KUSUMA HUSADA SURAKARTA - Romadhon, Nur; Istiningtyas, Anita; Agussafutri, Wahyu Dwi (Universitas Kusuma Husada Surakarta, 2020)
University student is one who is in the process of gaining knowledge or of learning and taking education at a higher education institution. The final-year students must even do a final project i.e. making a scholarly writing named skripsi. The problems that they encounter inhibit them to accomplish their final project, and this leads to their stress. Quran murrotal(Quran recitation) therapy is a complementary therapy to deal with stress. This therapy can be done through three ways:Quran directly recited by a therapist, Quran recited directly by a patient, and Quran recitation played from a recording. This research aims to investigate the difference of effect between tilawah therapy and murrotal therapy on stress level of the final-year students of KusumaHusada College of Health Sciences of Surakarta This research used the quasi experimental research method with two group pretest-posttest without control design. Purposive sampling was used to determine its samples. They consisted of 66 respondents. The data of the research were analyzed by using the Wilcoxon’sTest andthe Mann Whitney’sTest. Prior to the administration of the murrotal therapy, 78.8% of students had a moderate stress level, and following that of murrotal therapy, 63.6% of them had a mild stress level. In addition, prior to the administration of tilawah therapy, 81.8% of the students had a moderate stress level, and following that of tilawah therapy, 75.8% of them had a mild stress level. The difference of the stress level prior to and following the administration of murrotal therapy was indicated by the p-value which was less than 0.05. It also applies to that of the stress level prior to and following the administration of tilawah therapy where the the p-value was less than 0.05, meaning that both therapies are effective to decrease the stress level of the final year students. The difference of stress level due to the administration of murrotal therapy and that of tilawah therapy was indicated by the ratio of their mean rank of 17.00:17.00 which was not different in term of their effectiveness to reduce the stress level. Thus, the murrotal therapy was as effective as the tilawahterapy to decrease the stress level of the final year students of KusumaHusada College of Health Sciences of Surakarta.